Acceptance of the use of silver fluoride among Brazilian parents of children with special health care needs - Potgieter, N.; Pereira, V.; Elias, R.; Charone, S.; Groisman, S. (Frontiers in Oral Health, 2024)
Background: Children with special health care needs including Down Syndrome, Autism Spectrum Disorder and Down Syndrome experience difficulties in receiving dental treatment. Silver Diamine Fluoride (SDF) and Silver Fluoride (SF) are a minimally invasive treatments options to arrest dental caries without sedation; local or general anaesthesia (GA). AIM: Evaluation of Brazilian's parents' acceptance of the use of SF in CSHCN. Methods: After receiving education on SF, 100 Parents of CSHCN completed a questionnaire concerning their acceptance of SF, in different dental situation. Result: Majority of parents (74,5%) agreed to the use of SF for their children.SF was more acceptable on posterior teeth (74,5%) when compared to its use on anterior teeth (43,1%). Parents accepted to use SF in order: to reduce infection and pain (82,4%); to avoid dental injection (72,5%) and treatment under GA (84,3%). The Majority of parents accepted the properties of SF (82,4%) and Silver (80,4%). Conclusion: Silver Fluoride was accepted as a treatment option for caries, by Brazilian parents of CSHCN.SF should be considered as a treatment option for caries limited to dentine for CSHCN, taking into consideration the individual needs and opinions with regard to aesthetics and exposure to fluoride and silver.